COLD COMPRESS REDUCES PAIN SCALE INSULIN INJECTION AMONG DIABETES MELLITUS CLIENTS IN A PUBLIC HEALTH CENTER - Faridha Alfiatur Rohmaniah; Fery Nanik Handayani; Diana Tri Lestari; Muhamad Jauhar ((IJP) Indonesia Jurnal Perawat, 2024)
Diabetes Mellitus is a chronic disease that is a threat to health due to increased morbidity and mortality rates. This disease burdens sufferers, families who care for them, and the country. Problems that often arise are pain as an effect of insulin injection. One of the interventions that can be done independently is a cold compress. To analyze the effect of cold compress on the pain scale of insulin injection. The research design used a quasi-experimental with a pretest and a post-test with a control group design. The study was conducted at the Mijen I Health Center in August 2024—a sample of 15 clients for each group through purposive sampling. Inclusion criteria were diagnosed with Diabetes Mellitus, blood sugar measurement results 120 mg/dl (fasting blood sugar) or 140 mg/dl (random blood sugar), and received insulin injection. Exclusion criteria were respondents who withdrew and consumed analgesic drugs. This research instrument used the Numeric Rating Scale. Researchers provided cold compress intervention with a temperature of 13-16 0 C once for 3 days. Data analysis using Wilcoxon and Mann-Whitney tests. Cold compresses have a significant effect on the insulin injection pain scale with a p = 0.008 (p 0.05). Cold compresses reduce the insulin injection pain scale. Health centers can develop interventions by providing cold compresses to treat pain caused by insulin injections.